Collective resilience following mine clearance in Kurdish Iraq. Issue 2 (8th June 2015) - Durham, Jo; White, Rob
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of the study was to identify the economic impacts of landmine clearance on household livelihoods and to present the qualitative findings of a study undertaken in the Kurdish region of Iraq. Design/methodology/approach – The sampling method followed a case series, purposive sampling design. Five recipient households were interviewed from different districts. In addition, purposively selected program staff (N = 4) and local community leaders (N = 2) were interviewed. When undertaking the thematic analysis of the Kurdish household qualitative interviews, it became very apparent that the Kurdish informants did not talk in terms of economic outcomes as a result of demining. The data were then re-analyzed using a narrative framework and reported in this paper. Findings – While the research sought a link between demining, livelihoods, poverty reduction and economic development, the respondents told another story. Their story focused on the social consequences of returning to their "grandfather's land". Participants' narratives told of resilience resulting from negotiation with the environment and the importance of regaining one's identity and hopes to heal in the face of adversity. Research limitations/implications – The findings cannot be generalized to all mine action program recipients but have salience for rural households in the site of inquiry. Originality/value – The paper is rare in illustrating the social benefits of post-conflict demining and its links with social capital and collective resilience.